In-silico analysis of cucumber (Cucumis sativus L.) Genome for WRKY transcription factors and cis-acting elements. (April 2020) - Govardhana, Mallu; Kumudini, Belur Satyan
Graphical abstract: Highlights: Total of 62 putative WRKY genes were identified in cucumber genome and classified in to three major groups (Group I, IIa-IIe and III). Physicochemical properties, variants of WD in identified WRKY proteins were analyzed and based on chemical nature, WRKY genes are serine rich proteins. STRING analysis were performed for selected CsWRKY for their protein-protein interactions. Cis-acting elements of CsWRKY genes were analyzed for their expression patterns under different growth, development and other environmental conditions. Abstract: WRKY genes, comprises one among a large clan of transcription factor (TFs) genes in the plant kingdom, playing a fundamental role in the vegetative and reproductive growth, development and stress responses of a plant. In spite of several studies on cucumber ( Cucumis sativus L.), WRKY genes and their interaction with stress response is limited. The present study, on the whole genome of cucumber was analyzed for WRKY genes which recognized 62 CsWRKY genes associated with the proteins obtained from lineages of supplementary plants. The physicochemical properties reveal the CsWRKY gene is ser-rich TF (6.70–18.40 %). The chromosomal distribution showed that all putative CsWRKY genes were distributed in seven chromosomes, enriched on chromosome 3 and 6 and least on chromosome 5. Based on phylogenetic analysis, along with motif determination and gene structure analysis, CsWRKY s are categorized as a Group I, II and III. The Group II further subdivided as Groups IIa-e. In the present study, it was observed that Group II WRKY-TFs was the largest group containing 43 WRKY genes containing a single WD (WRKY domain - WRKYGQK/WRKYGKK) and C2 H2 type zinc finger structure (C-X4-5 -C-X23 -H-X1 -H). The data also revealed that chromosome 3 and 5 contained all the three major groups and chromosome 6 contained I and II WRKY genes with uneven distribution. STRING analysis of selected CsWRKY proteins expressed in response to abiotic stress interacts with the CsMAPK proteins. Analysis of cis -acting elements and results suggest that CSWRKY genes play important role in response to biotic and abiotic stress. Response also predicted the candidate gene expression in cucumber during its development under different cellular condition.